Effect of incentive spirometry versus inspiratory muscle Training on inspiratory muscle strength In elderly individuals - DR. ANKITA DABSHEDE,; DR.VISHNU VARDHAN,; DR.TUSHAR PALEKAR, (International Journal of Pharma and Bio Sciences, 2018)
The respiratory system comprises primarily the thoracic cage, lungs and diaphragm. Total respiratory system compliance includes lung and chest wall compliance. With aging there are structural changes to the thoracic cage causing reduction in the chest wall compliance. The diaphragm is the most important respiratory muscle and plays an essential role during inspiration. Diaphragmatic strength with age is related to muscle atrophy and age related decline in diaphragmatic strength may predispose older individuals to diaphragmatic fatigue and ventilatory failure during increased ventilatory load on the respiratory system. 50 subjects of age group 60-74 years were selected by convenient sampling. Intervention was given for inspiratory muscle training on inspiratory muscle strength by using inspiratory muscle threshold device and volume oriented incentive spirometer. Statistical analysis was done by using t test and unpaired t test. Significant improvement in pre and post treatment of PImax(p=0.061) was observed.This study concludes that inspiratory muscle training with incentive spirometry and inspiratory muscle training by IMT threshold device, both are effective in improving inspiratory muscle strength but when both the groups are compared between the groups, inspiratory muscle training with IMT threshold device along with incentive spirometry is more effective.